2009
DOI: 10.1007/s10828-009-9032-x
|View full text |Cite
|
Sign up to set email alerts
|

Verb clusters in colloquial German

Abstract: Although verb cluster formation has long been a topic of syntactic research, many of its properties are still controversial. In this paper, we contribute to the ongoing discussion by looking at verb order variation in 3-and 4-verb clusters in German on the basis of new empirical evidence. First, we present several experiments that have used the method of speeded grammaticality judgments in order to determine the orders within a verb cluster that are accepted by native speakers. A major result of our experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…Because auxiliary inversion in verb clusters is known to involve a large amount of dialectal variation (see Schmid & Vogel 2004), Bader & Schmid (2009) also looked at the regional background of their participants. Since the pattern of well-formedness just described was found to be independent of participants' regional background, Bader & Schmid (2009) concluded that the order 3-1-2 is an optional variant in Colloquial German although not in Standard German. The remaining four orders received rather low judgments but still showed certain gradations which will be discussed later.…”
Section: Subexperiments C : Verb-cluster Linearizationmentioning
confidence: 99%
“…Because auxiliary inversion in verb clusters is known to involve a large amount of dialectal variation (see Schmid & Vogel 2004), Bader & Schmid (2009) also looked at the regional background of their participants. Since the pattern of well-formedness just described was found to be independent of participants' regional background, Bader & Schmid (2009) concluded that the order 3-1-2 is an optional variant in Colloquial German although not in Standard German. The remaining four orders received rather low judgments but still showed certain gradations which will be discussed later.…”
Section: Subexperiments C : Verb-cluster Linearizationmentioning
confidence: 99%
“…Bader & Schmid (2009) show that speakers from all German speaking regions give the 312 order a high acceptability rating, though not as high as for the 132 order.…”
Section: Order Preferences In German 3-verb Clustersmentioning
confidence: 82%
“…For German, the syntactic evidence for this distinction is particularly controversial and some accounts consider all these types of verbs as projecting VP structures (see Sternefeld 2006: 507ff.). In order to understand the behavior of verbal clusters, it is useful to conflate the different categories of verbs assuming that they create projections of the same type embedded in each other; see (9) (see previous analyses of verb clusters in this vein ;Haider 2003;Schmidt & Vogel 2004;Bader & Schmid 2009;Salzmann 2013 The frequencies of functional and lexical verbs in our dataset are reported in Table 5. Simple lexical verbs without any functional verb occur more frequently in non-public (68%) than in public texts (57.1%); see Table 7.…”
Section: Overview Of the Datamentioning
confidence: 99%